Does Locke Have an Akrasia Problem? - Samuel C. Rickless (Journal of Modern Philosophy)
Starting in the second edition of the Essay, Locke becomes interested in the phenomenon of akrasia, or weakness of will. As he conceives it, akrasia occurs when we will something contrary to what we acknowledge to be our greater good. This commitment represents an important shift from the first edition of the Essay, where Locke argues that the will is always determined by a judgement of our greater good. But traces of the first-edition view are present even in the second edition, so much so that it is unclear whether Locke is entitled to an explanation of akrasia at all. In this essay, we propose a new interpretation of Locke’s account of akrasia, one that mediates between his seemingly conflicting commitments. We believe that this interpretation represents an improvement over past interpretations, which make Locke’s conception of akrasia too weak to do the work he intends for it. Moreover, getting Locke’s account of akrasia right allows us to gain clarity on his view of the will, a subtle and ultimately quite plausible part of his moral psychology.